2003
DOI: 10.1897/02-450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of toxic products of anthracene photomodification in simulated sunlight

Abstract: Currently, the evidence of a rapid photomodification of anthracene under sunlight resulting in enhanced toxicity exists; however, the chemical causes of toxicity are still unknown. The present study aimed at filling this gap by irradiation of an anthracene suspension with simulated sunlight and subsequent effect-directed fractionation and analysis of toxic products with respect to the inhibition of bacterial energy metabolism of Vibrio fischeri, reproduction of the green algae Scenedesmus vacuolatus, and genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
3
44
0
1
Order By: Relevance
“…Appropriate alternatives applied for genotoxicity identification are the umu-test on the basis of the activation of the SOS DNA repair system in Salmonella typhimurium TA1535/pSK1002 [68,111,112] and the Mutatox assay using a dark mutant strain of Vibrio fischeri [36,77]. Both are promising approaches with respect to high-throughput analysis even if the discriminating power is lower than that of the multi-strain Ames approach.…”
Section: Genotoxicity and Mutagenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Appropriate alternatives applied for genotoxicity identification are the umu-test on the basis of the activation of the SOS DNA repair system in Salmonella typhimurium TA1535/pSK1002 [68,111,112] and the Mutatox assay using a dark mutant strain of Vibrio fischeri [36,77]. Both are promising approaches with respect to high-throughput analysis even if the discriminating power is lower than that of the multi-strain Ames approach.…”
Section: Genotoxicity and Mutagenicitymentioning
confidence: 99%
“…The recording of ultraviolet (UV) absorption spectra after separation by HPLC is also a powerful tool for the identification of compounds with noncharacteristic mass spectra such as many polyaromatic compounds [13,86]. Functional groups of analytes may be identified by recording infrared absorption spectra [13,112].…”
Section: Chemical Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Im Falle polyaromatischer Verbindungen liefern UV-Absorptionsspektren wichtige Informationen über das aromatische Grundgerüst (Holmborn et al, 1984;Brack und Schirmer, 2003). Funktionelle Gruppen lassen sich durch den Einsatz von IR-Absorptionsspektren gewinnen (Brack et al, 2003a;Holmborn et al, 1984).…”
Section: Chemische Identifizierungunclassified
“…Incidentally, authors reported observing a higher toxicity after the biodegradation of CA than before the microbiological treatment of effluent (Arroyo-Figueroa et al, 2011). The fact that hydroxylated anthraquinones have presented significant toxicity is important because these compounds can be photoproducts of CA (Brack et al, 2003). This fact makes the identification of the compounds produced during the degradation of CA necessary.…”
Section: Introductionmentioning
confidence: 99%